Menakar Konstitusionalitas sebuah Kebijakan Hukum Terbuka dalam Pengujian Undang-Undang - Wibowo, Mardian (Jurnal Konstitusi, 2015)
This study attempts to elaborate the definition of the â€œopen legal policyâ€ concept which has stated by the Constitutional Court as the autonomy of the Law- making body whenever UUD 1945 as the constitution did not regulate particular substances of a Law that is being made. In order to prevent this autonomy leans toward arbitrariness, it is necessary to establish a model of review towards open legal policies. One feasable option that the Constitutional Court could adapt is the "maximin" strategy (selecting the best option in numbers of bad possibilities) which is developed from the rational choice approach.